Official opening ceremony of the “Devil Island” Project, Tasmania, May 2008 - Englefield, Bruce (European Journal of Oncology and Environmental Health, 2008)
Tasmanian Devils have been in peril since the late 1990s and are facing extinction in the wild in ten to twenty years from a cancer, if nothing changes. Labelled the Devil Facial Tumour Disease (DFTD), it is transmitted only by biting between Devils...